The role of the coach-athlete relationship during rehabilitation following severe knee injury in adolescent athletes - King, Jamie (Division of Exercise Science and Sports Medicine, 2025)
Background: Severe knee injury requires prolonged rehabilitation and absence from sport. Coaches are vital during rehabilitation, supporting athletes with psychological challenges associated with injury recovery. While athletes appreciate coaches' involvement during rehabilitation, their satisfaction with the support delivered is varied. The coach-athlete dyad is the most instrumental relationship in sport, whereby thoughts, feelings and actions are unified to achieve success and satisfaction. Although coach-athlete relationships have been explored, research on coach-athlete relationships during rehabilitation is scarce. Furthermore, influences amongst amateur coaches and adolescent athletes are unclear. Scoping review: To explore the coach's role during an athlete's rehabilitation from injury, a scoping review was conducted using EBSCOhost, PubMed and Scopus databases. A total of 2716 studies were excluded based on eligibility criteria during title, abstract and full-text screening. Twenty-seven articles were included for review. Factors that may influence the coach's role during rehabilitation included athlete's and coaches' age and gender; type of sport and level of competition; the athletes' role in the team; and injury severity and type. The coach's major role during rehabilitation was providing social support to injured athletes. The amount and availability of social support, as well as differing forms and their perceived prominence to athletes' wellbeing, are key features to consider. Social support provided by coaches to athletes undergoing rehabilitation aided in maintaining coachathlete relationships, and in preventing conflict between the two upon return to sport. Aim and objectives: We then conducted a qualitative study to explore the role of the coach-athlete relationship to determine its influences on rehabilitation following severe knee injury. The objectives were to explore the psychological influences of severe knee injury on rehabilitation in adolescent athletes and their coaches; to explore coaches' and athletes' perspectives and understanding of their respective roles during rehabilitation; and to describe factors that influence coach-athlete relationships during rehabilitation following severe knee injury. Methodology: Nine coach-athlete relationships were recruited via email from well-resourced schools in South Africa. Semi-structured interviews were conducted in-person and recorded via Zoom. Nvivo 12 was utilised to organise, store and analyse the data. An inductive approach to reflexive thematic analysis was employed. Results: The type, timing, amount and quality of social support provided by coaches influenced coachathlete relationships during rehabilitation. Athletes expressed a lack of coach support, while coaches were unsure of how much support to offer. Novice coaches and athletes had insufficient knowledge regarding injury rehabilitation and preserving coach-athlete relationships. Failure to maintain social inclusion in the team and absence of a person-centered approach affected coach-athlete relationship quality. Athletes' reliance on coach-athlete relationships during rehabilitation was impacted by their supportive families and physiotherapists. Ensuring regular communication was vital to uphold coachathlete relationships during rehabilitation. Yet, coaches prioritised the team and were uncertain of their commitment to injured athletes owing to lengthy injury timelines. Coach-athlete relationships were also affected by school's policies to safeguard adult-minor interactions. Part-time coaches had additional commitments which took preference above preserving coach-athlete relationships throughout rehabilitation. Conclusion: The coach-athlete relationship was used to facilitate athlete's psychological coping linked with severe knee injury and rehabilitation. Coaches provided injured athletes with social support, yet athletes' contentment with their coaches' contributions during rehabilitation was mixed. The coachathlete relationship may influence rehabilitation by improving experiences with injury recovery, enhancing wellbeing, and facilitating a smooth transition into return to sport. We recommend upskilling coaches and implementing a ‘team approach' during rehabilitation to enhance coachathlete relationships. Future research should consider diverse samples; follow-up interviews; validating instruments within rehabilitation contexts; and the impact of gender, socioeconomic status, resource access, and ethical dilemmas.